Distinct effects of acute pretreatment with lipophilic and hydrophilic statins on myocardial stunning, arrhythmias and lethal injury in the rat heart subjected to ischemia/reperfusion - Čarnická, S; Adameová, A; Nemčeková, M; Matejíková, J; Pancza, D; Ravingerová, T (Physiological research, 2011)
Although both lipophilic and more hydrophilic statins share the same pathway of the inhibition of HMG-CoA reductase, their pleiotropic cardioprotective effects associated with the ability to cross cellular membranes, including membranes of heart cells, may differ. To test this hypothesis, isolated rat hearts were Langendorff-perfused either with simvastatin (S, 10 micromol/l) or pravastatin (P, 30 micromol/l), 15 min prior to ischemia. Control untreated hearts (C) were perfused with perfusion medium only. Postischemic contractile dysfunction, reperfusion-induced ventricular arrhythmias and infarct size were investigated after exposure of the hearts to 30-min global ischemia and 2-h reperfusion. Both lipophilic S and hydrophilic P reduced the severity of ventricular arrhythmias (arrhythmia score) from 4.3 +/- 0.2 in C to 3.0 +/- 0 and 2.7 +/- 0.2 in S and P, respectively, (both P < 0.05), decreased the duration of ventricular tachycardia and suppressed ventricular fibrillation. Likewise, the extent of lethal injury (infarct size) determined by tetrazolium staining and expressed in percentage of risk area, was significantly lower in both treated groups, moreover, the effect of P was more pronounced (27 +/- 2 % and 10 +/- 2 % in S and P groups, respectively, vs. 42 +/- 1 % in C; P < 0.05). In contrast, only S, but not P, was able to improve postischemic recovery of left ventricular developed pressure (LVDP; 48 +/- 12 % of preischemic values vs. 25 +/- 4 % in C and 21 +/ -7 % in P groups; P < 0.05). Our results suggest that differences in water solubility of statins indicating a different ability to cross cardiac membranes may underlie their distinct cardioprotective effects on myocardial stunning and lethal injury induced by ischemia/reperfusion.
Keywords: krysa rodu Rattus; mužské pohlaví; míra přežití; Male; výsledek terapie; syndrom omráčeného myokardu; Myocardial Reperfusion Injury; premedikace; Hydrophobic and Hydrophilic Interactions; reperfuzní poškození myokardu; Rats; Hydroxymethylglutaryl-CoA Reductase Inhibitors; potkani Wistar; Arrhythmias, Cardiac; Animals; zvířata; Treatment Outcome; Myocardial Stunning; Rats, Wistar; Survival Rate; srdeční arytmie; hydrofobní a hydrofilní interakce; statiny; Premedication